PENYELENGGARAAN URUSAN PEMERINTAHAN BIDANG PERTAMBANGAN DALAM PERSPEKTIF OTONOMI DAERAH - Djambar, Djambar (Katalogis, 2017)
The research was to identify and analyze whether or not the assignment of authorities in governance of mining affairs from the City/Regency Government to Provincial Government or National Government has been consistent with the objectives of local autonomy policies and identify and analyze the implications of the assignment of authorities in governance of mining affairs from the City/Regency Government. It was a normative research adobting legal approach, historical approach and conseptual approach. With reference to the research findings, it was concludedÂ that (1) the assignment of authorities in governance of mining affairs from the City/Regency Government to Provincial Government or National Goverment was not consistent with the objectives of local autonomy policies, and (2) the assignment of authorities in governance of mining affairs form the City/Regency Government to Provincial Government or National Government brought implicationts to modification of institutional structures in the City/Regency, adjustments to prevailing law and regulationts, loss of authority to issue Mining Business Permit, modifications to development plans, decrease of City/Regency revenues, and trigger of conflicts among City/Regency Government, Provincial Government and National Government.